Dietary choline intake and colorectal cancer: a cross-sectional study of 2005–2018 NHANES cycles - Xu, Xijuan; Ying, Hongan; Huang, Lili; Hong, Weiwen; Chen, Wenbin (Frontiers in Nutrition, 2024)
Background It remains unclear if choline intake is associated with colorectal cancer. Therefore, we examined data from the National Health and Nutrition Examination Survey (NHANES). Methods This cross-sectional study included 32,222 U.S. adults in the 2005–2018 NHANE cycles, among whom 227 reported colorectal cancer. Dietary choline was derived from 24-h recalls. Logistic regression estimated odds of colorectal cancer across increasing intake levels, adjusting for potential confounders. Results After adjusting for sociodemographic variables, BMI, alcohol use, smoking status, comorbidities, and dietary factors (energy, fat, fiber, and cholesterol), the odds ratio (OR) for colorectal cancer was 0.86 (95% CI: 0.69–1.06, p = 0.162) per 100 mg higher choline intake. Across increasing quartiles of choline intake, a non-significant inverse trend was observed (Q4 vs. Q1 OR: 0.76, 95%CI: 0.37 ~ 1.55, P-trend = 0.23). Subgroup analyses revealed largely consistent associations, with a significant interaction by hypertension status (P-interaction =0.022). Conclusion In this large, nationally representative sample of U.S. adults, higher dietary choline intake was not significantly associated with colorectal cancer odds after adjusting for potential confounders. However, a non-significant inverse trend was observed. Further prospective studies are needed to confirm these findings and elucidate the underlying mechanisms.